Investigational Medicinal Products for the Inner Ear: Review of Clinical Trial Characteristics in ClinicalTrials.gov - Le Prell, Colleen G. (Journal of the American Academy of Audiology, 2021)
Background The previous 30 years have provided information on the mechanisms of cell death in the inner ear after noise exposure, ototoxic drug injury, and during aging, and clinical trials have emerged for all of these acquired forms of hearing loss. Sudden hearing loss is less well understood, but restoration of hearing after sudden hearing loss is also a long-standing drug target, typically using steroids as an intervention but with other agents of interest as well.Purpose The purpose of this review was to describe the state of the science regarding clinical testing of investigational medicinal products for the inner ear with respect to treatment or prevention of acquired hearing loss.Data Collection and Analysis Comprehensive search and summary of clinical trials listed in the National Library of Medicine (www.ClinicalTrials.gov) database identified 61 clinical trials.Results Study phase, status, intervention, and primary, secondary, and other outcomes are summarized for studies assessing prevention of noise-induced hearing loss, prevention of drug-induced hearing loss, treatment of stable sensorineural hearing loss, and treatment of sudden sensorineural hearing loss.Conclusion This review provides a comprehensive summary of the state of the science with respect to investigational medicinal products for the inner ear evaluated in human clinical trials, and the current challenges for the field.
Keywords: otoacoustic emissions; clinical trial; ototoxicity; noise induced hearing loss; investigational medicinal product; sensorineural hearing loss